(3GdCeGf ef CNWGQ GdCSaGQ hGdCReGfs - (3GdWGhSj, GdMSfj, CHh GdbGSe, QVi GdnqOjf, Ydj Hf ehSi Hf LYaQ Hf WGhhS, J (B664 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3jbhd ehdGfG GdbGSe Ydj Hf ehSi(B... (3GdMeO ddg GdPj GSJLGQJ Hg GdCQhGM(B... (3hHYO, aEfj hLOJ GdEfSGf eSGaQG eP NQL ef GdhLhO(B...s
(3BNQgG (B:s
(3GdHGH GdQGHY YTQ(B... (3aGdChdi deKdc eYQaI gPg GdYdGLGJ hGdGSJXgGQ HgPg GdCOhjIh GdCTQHI hGddg CSFd Cf jJaVd Ydjc(B... (3HGdSYGOI(B... (3Efg Ydi eG jTGA bOjQ(B...s
(3JNddgG ChQGb HZjQ MOjK eZGjQs
(3JHUQI GdeDda (B:s
(3dg ef GdcJH(B: (3adGM GdSGFd hfLGM GdeSGFd, hGdCSQGQ GdehOYI aj SGYGJ Gddjd hGdfgGQ, GfXQ U(B255s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, U(B26s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B479s
Keywords: (3GdJUha hGdBOGH GdTQYjIs